Determinación de la incidencia de la gestión por resultados en el cumplimiento de las metas del Hospital Básico Chone periodo 2018-2019 - Pazmiño Rodríguez, María Fernanda (2022)
The stated objective was to evaluate the incidence of management by results of the Chone Basic Hospital (HBCH) in the period 2018-2019 to address this problem, meta-analysis techniques were used to define the management model, correspondence analysis method to establish compliance of indicators, the correlation was determined using the Pearson method, the managers were interviewed. A survey was conducted to HBCH officials and the variables used were validated using Cronbach's alpha. Principal component analysis was used to interpret the survey and the Ishikawa diagram was made. The management model of the HBCH was the Government for Integrated Results (GPRI). No statistical significance was found between the budget committed and completed for the year 2018. While, in 2019, a high statistical significance was detected for non-compliance with what was planned, executing 9.23% of what was planned, 32.31% more than was done committed and finally 58.46% was partially fulfilled. The Ishikawa diagram detected the lack of progressive, transversal, portfolio, trend and perception survey monitoring. Impact Assessment and leadership commitment. In Ecuador, very little is understood about how employees perceive the advantages and disadvantages of compensation and its overall impact on work behavior to comply with the GRPI. This study aims to be a contribution to Art. 51. Competence of the Ministry of Labor Relations in the scope of the LOSEP subsections d), h) i).